Ultra-high energy neutrinos at the Pierre Auger Observatory - Pieroni, Pablo Emanuel (2016)
Neutrinos in the sub-EeV energy range and above can be detected with the Surface Detector (SD) of the Pierre Auger Observatory. They can be identified through the broad time structure of the signals induced in the SD stations. This can be efficiently done for neutrinos of all flavours interacting in the atmosphere at large zenith angles, typically above 60 deg. (downward going), as well as for ?Earth-skimming? neutrino interactions in the case of tau neutrinos (upward going). The wide angular range naturally calls for three sets of identification criteria designed to search for downward going neutrinos in the zenith angle bins (60, 75) deg. and (75, 90) deg. as well as for upward going neutrinos. In this contribution the three searches are combined into a single one, providing, in the absence of candidates in data, an updated and stringent limit to the flux of ultra-high energy neutrinos.